Saúde e Qualidade de Vida: o Uso de Plantas e “Bichos” por Famílias da Vila do Abade – Curuçá/PA - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2014)
This article aimed to understand, through ethnography, the medicine practices by families living in Village of Abade, in a town in Curuçá/PA, in order to contribute to elaboration and/or management of Politics of Public health. The use of plants is not limited for the “cure of diseases”, but for the prevention. The relationship with “animals” is involved by symbolism. This relantionship provides the acess or maintence of quality of life and this concept suffered changes, inserting the characteristics of welfare for this families. In this ethnography of medicine practices, people have considered the possibility of coexistence between the traditional and scientific knowledge.
Health and Quality of Life: The use of Plants and Animals by Families at Abade Village - Curuçá/PA
Keywords: Flora e Fauna; Saúde-Doença; Qualidade de Vida; CNPQ::CIENCIAS HUMANAS